SPIRITUAL AND PEDAGOGICAL ROLE OF SELF-EDUCATION IN THE FORMATION OF GENERAL SECONDARY SCHOOLS STUDENTS AS PERFECT PERSONS - Zaripova Gulbahor Kamilovna (Journal of new century innovations, 2024)
Abstract: This article is devoted to a detailed presentation of scientific and practical research and theoretical research of the author on the role of self-education in the system of spiritual and educational upbringing of secondary school students. At the same time, it is stated that the development of pedagogical and psychological foundations of a system that regulates activities that form the basis for independent thinking of students is an urgent problem of scientific research, and scientific and practical research to solve this problem is relevant.